29 171 x 4 y y y y y 03 02 1 014 171 010 x 3 2 1 0

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ce the roots are x = −2.45, 0.65, 2.75. f (x) = 2 2x5 + 5x3 + 14x2 + 30x − 7 . Points of inflection will occur when the numerator changes sign, (x2 + 1)5/2 since the denominator is always positive. A plot of y = 2x5 + 5x3 + 14x2 + 30x − 7 suggests that there is only one root and it lies in [0, 1]. Subdivide into ten subintervals and determine that the root lies between x = 0.2 and x = 0.3. Thus to one decimal place the point of inflection is located at x = 0.25. f (x) = f (x1 ) − f (x2 ) = x2 − x2 = (x1 + x2 )(x1 − x2 ) < 0 if x1 < x2 for x1 , x2 in [0, +∞), so f (x1 ) < f (x2 ) 1 2 and f is thus increasing. 46. f (x1 ) − f (x2 ) = is decreasing. 1 1 x2 − x1 − = > 0 if x1 < x2 for x1 , x2 in (0, +∞), so f (x1 ) > f (x2 ) and thus f x1 x2 x1 x2 145 47. Chapter 5 (a) If x1 < x2 where x1 and x2 are in I , then f (x1 ) < f (x2 ) and g (x1 ) < g (x2 ), so f (x1 ) + g (x1 ) < f (x2 ) + g (x2 ), (f + g )(x1 ) < (f + g )(x2 ). Thus f + g is increasing on I . (b) Case I: If f and g are ≥ 0 on I , and if x1 < x2 where x1 and x2 are in I , then 0 < f (x1 ) < f (x2 ) and 0 < g (x1 ) < g (x2 ), so f (x1 )g (x1 ) < f (x2 )g (x2 ), (f · g )(x1 ) < (f · g )(x2 ). Thus f · g is increasing on I . Case II: If f and g are not necessarily positive on I then no conclusion can be drawn: for example, f (x) = g (x) = x are both increasing on (−∞, 0), but (f · g )(x) = x2 is decreasing there. 48. (a) f (x) = x, g (x) = 2x 49. (a) (b) f (x) = x, g (x) = x + 6 (c) f (x) = 2x, g (x) = x b b f (x) = 6ax + 2b = 6a(x + ), f (x) = 0 when x = − . f changes its direction of concavity 3a 3a b b so − is an inflection point. at x = − 3a 3a (b) If f (x) = ax3 + bx2 + cx + d has three x-intercepts, then it has three roots, say x1 , x2 and x3 , so we can write f (x) = a(x − x1 )(x − x2 )(x − x3 ) = ax3 + bx2 + cx + d, from which it follows that 1 b = (x1 + x2 + x3 ), which is the average. b = −a(x1 + x2 + x3 ). Thus − 3a 3 (c) f (x) = x(x2 − 3x2 + 2) = x(x − 1)(x − 2) so the intercepts are 0, 1, and 2 and the average is 1. f (x) = 6x − 6 = 6(x − 1) changes sign at x = 1. 50. b f (x) = 6x + 2b, so the point of inflection is at x = − . Thus an increase in b moves the point of 3 inflection to the left. 51. (a) Let x1 < x2 belong to (a, b). If both belong to (a, c] or both belong to [c, b) then we have f (x1 ) < f (x2 ) by hypothesis. So assume x1 < c < x2 . We know by hypothesis that f (x1 ) < f (c), and f (c) < f (x2 ). We conclude that f (x1 ) < f (x2 ). (b) Use the same argument as in part (a), but with inequalities reversed. 52. By Theorem 5.1.2, f is increasing on any interval ((2n − 1)π, 2(n + 1)π ) (n = 0, ±1, ±2, · · ·), because f (x) = 1 + cos x > 0 on [(2n − 1)π, (2n + 1)π ]. By Exercise 51 (a) we can piece these intervals together to show that f (x) is increasing on (−∞, +∞). 53. t = 7.67 1000 0 15 0 54. By zooming on the graph of y (t), maximum increase is at x = −0.577 and maximum decrease is at x = 0.577. 55. 56. y y 4 2 infl pt 3 1 t infl pts 2 1 x Exercise Set 5.2 146 EXERCISE SET 5.2 1. (a) (b) y y f (x) f (x) x x (c) (d) y y f (x) f (x) x 2. (a) x (b) y y x x (c) (d) y y x x 4. (a) f (x) = 6x − 6 and f (x) = 6, with f (1) = 0. For the first derivative test, f < 0 for x < 1 and f > 0 for x > 1. For the second derivative test, f (1) > 0. (b) 3. f (x) = 3x2 − 3 and f (x) = 6x. f (x) = 0 at x = ±1. First derivative test: f > 0 for x < −1 and x > 1, and f < 0 for −1 < x < 1, so there is a relative maximum at x = −1, and a relative minimum at x = 1. Second derivative test: f < 0 at x = −1, a relative maximum; and f > 0 at x = 1, a relative minimum. (a) f (x) = 2 sin x cos x = sin 2x (so f (0) = 0) and f (x) = 2 cos 2x. First derivative test: if x is near 0 then f < 0 for x < 0 and f > 0 for x > 0, so a relative minimum at x = 0. Second derivative test: f (0) = 2 > 0, so relative minimum at x = 0. (b) g (x) = 2 tan x sec2 x (so g (0) = 0) and g (x) = 2 sec2 x(sec2 x + 2 tan2 x). First derivative test: g < 0 for x < 0 and g > 0 for x > 0, so a relative minimum at x = 0. Second derivative test: g (0) = 2 > 0, relative minimum at x = 0. (c) 5. Both functions are squares, and so are positive for values of x near zero; both functions are zero at x = 0, so that must be a relative minimum. (a) f (x) = 4(x − 1)3 , g (x) = 3x2 − 6x + 3 so f (1) = g (1) = 0. (b) f (x) = 12(x − 1)2 , g (x) = 6x − 6, so f (1) = g (1) = 0, which yields no information. (c) f < 0 for x < 1 and f > 0 for x > 1, so there is a relative minimum at x = 1; g (x) = 3(x − 1)2 > 0 on both sides of x = 1, so there is no relative extremum at x = 1. 147 Chapter 5 (a) f (x) = −5x4 , g (x) = 12x3 − 24x2 so f (0) = g (0) = 0. (b) f (x) = −20x3 , g (x) = 36x2 − 48x, so f (0) = g (0) = 0, which yields no information. (c) 6. f < 0 on bot...
View Full Document

This document was uploaded on 02/23/2014 for the course MANAGMENT 2201 at University of Michigan.

Ask a homework question - tutors are online